Quality Assurance Analysis Using The Six Sigma Dmaic Method To Reduce Product Defects - Dedy Ariyanto; Hery Irwan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Forklifts are essential material handling equipment that play a significant role in supporting operational activities in manufacturing companies. The high intensity of forklift usage increases the risk of equipment failure, resulting in higher downtime and reduced operational effectiveness. This study aims to analyze the operational effectiveness of Forklift 1 using the Overall Equipment Effectiveness (OEE) method and to propose maintenance improvements to enhance forklift reliability and operational performance. This research employs the Overall Equipment Effectiveness (OEE) method, which consists of three main indicators: Availability Rate, Performance Efficiency, and Quality Rate. The data were collected through observations, interviews, documentation, and historical records of Forklift 1 operations and maintenance. The results indicate that before the proposed maintenance improvements were implemented, the OEE values were relatively low, reaching 36.9% in October, 63.8% in November, and 18.8% in December. After implementing a preventive maintenance schedule based on 540 operating hours, the OEE values improved significantly to 99.8% in January, 81.2% in February, and 99.8% in March. These findings demonstrate that the implementation of the OEE method effectively improves forklift operational performance by reducing downtime, increasing equipment reliability, and optimizing maintenance scheduling. Therefore, the OEE method can serve as an effective reference for improving productivity and operational efficiency in manufacturing companies.